Về sai số của mô hình mờ - Hồ, Nguyễn Cát; Sơn, Trần Thái (Journal of Computer Science and Cybernetics, 2016)
Some researchers used a set of fuzzy conditional implications of the form of IF-THEN sentence with linguistic values to model a real process. Then it causes some errors of a fuzzy model, called model error. In this paper we have examined the  model error, introduced a more stable method to determine it and investigated some its properties.